Proteomic Analysis of Human Neural Stem Cell Differentiation by SWATH-MS - Tyleckova, Jirina; Cervenka, Jakub; Poliakh, Ievgeniia; Novak, Jaromir; Kepkova, Katerina Vodickova; Skalnikova, Helena Kupcova; Vodicka, Petr (Methods in molecular biology (Clifton, N.J.), 2022)
The unique properties of stem cells to self-renew and differentiate hold great promise in disease modelling and regenerative medicine. However, more information about basic stem cell biology and thorough characterization of available stem cell lines is needed. This is especially essential to ensure safety before any possible clinical use of stem cells or partially committed cell lines. As proteins are the key effector molecules in the cell, the proteomic characterization of cell lines, cell compartments or cell secretome and microenvironment is highly beneficial to answer above mentioned questions. Nowadays, method of choice for large-scale discovery-based proteomic analysis is mass spectrometry (MS) with data-independent acquisition (DIA). DIA is a robust, highly reproducible, high-throughput quantitative MS approach that enables relative quantification of thousands of proteins in one sample. In the current protocol, we describe a specific variant of DIA known as SWATH-MS for characterization of neural stem cell differentiation. The protocol covers the whole process from cell culture, sample preparation for MS analysis, the SWATH-MS data acquisition on TTOF 5600, the complete SWATH-MS data processing and quality control using Skyline software and the basic statistical analysis in R and MSstats package. The protocol for SWATH-MS data acquisition and analysis can be easily adapted to other samples amenable to MS-based proteomics.
Keywords: buněčná diferenciace; Software; Neural stem cell; software; proteom; Humans; Mass spectrometry; řízení kvality; Proteomics; Neural differentiation; Neural Stem Cells; lidé; Spectral library; proteomika; SWATH-MS; nervové kmenové buňky; Skyline; Quality Control; Cell Differentiation; Data independent acquisition; Proteome; hmotnostní spektrometrie; Mass Spectrometry